Polio elimination in Nigeria: A review - Nasir, Usman Nakakana (Hum Vaccin Immunother, 2015)
Nigeria has made tremendous strides towards eliminating polio and has been free of wild polio virus (WPV) for more than a year as of August 2015. However, sustained focus towards getting rid of all types of poliovirus by improving population immunity and enhancing disease surveillance will be needed to ensure it sustains the polio-free status. We reviewed the pertinent literature including published and unpublished, official reports and working documents of the Global Polio Eradication Initiative (GPEI) partners as well as other concerned organizations. The literature were selected based on the following criteria: published in English Language, published after year 2000, relevant content and conformance to the theme of the review and these were sorted accordingly. The challenges facing the Polio Eradication Initiative (PEI) in Nigeria were found to fall into 3 broad categories viz failure to vaccinate, failure of the Oral Polio Vaccine (OPV) and epidemiology of the virus. Failure to vaccinate resulted from insecurity, heterogeneous political support, programmatic limitation in implementation of vaccination campaigns, poor performance of vaccination teams in persistently poor performing Local Government areas and sporadic vaccine refusals in Northern Nigeria. Sub optimal effectiveness of OPV in some settings as well as the rare occurrence of VDPVs associated with OPV type 2 in areas of low immunization coverage were also found to be key issues. Some of the innovations which helped to manage the threats to the PEI include a strong government accountability frame work, change from type 2 containing OPV to bi valent OPVs for supplementary immunization activities (SIA), enhancing environmental surveillance in key states (Sokoto, Kano and Borno) along with an overall improvement in SIA quality. There has been an improvement in coverage of routine immunization and vaccination campaigns, which has resulted in Nigeria being removed from the list of endemic countries following an absence of new cases for an entire year as of September 2015. However, the last mile remains to be crossed and there is need to further improve and sustain the momentum to complete the journey toward polio elimination.